Analysis of the influence of the picture layout on the visual tracking of children and young people with cerebral palsy - Audi, Mauro [UNESP]; Sankako, Andreia N. [UNESP]; Spiller, Marcelo G. [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (My University, 2019)
The study investigated the effects of size, number and target displays on the accuracy and time required for the selection of information on a computer screen by students with cerebral palsy. Participants were 17 students with cerebral palsy of both sexes, aged between 6 and 12 years. Data were collected on the mean time of first fixation, mean before fixation, mean for total fixation duration, mean for fixation count, and mean for visit duration time, which were exported to GraphPad V4 software. The non-parametric Kruskal-Wallis test was used for the statistical analysis, followed by Dunn's multiple comparison test. The result was significant when comparing the visualization of the upper and lower quadrants in relation to the middle and lower quadrants of the screen; no significant difference was found for the results comparing the upper and lower quadrants, on the right and left sides, of the size of the displayed images. It was concluded that all participants had better performance in the gaze focus by fixing the eyes on the images displayed on the upper and lower lateral quadrants of the screen, and worse performance in the quadrants placed in the center of the screen, especially the lower center quadrant.
Keywords: Augmentative and alternative communication; Cerebral palsy; Display design